Thermodynamic behaviour of zinc and cadmium in liquid-Te-saturated CdTeZnTe solid solutions - Shamsuddin M.; Gupta T.K.S.P.; Nasar A.; Ramachandrarao P. (My University, 2025)
The activity of zinc in liquid-tellurium-saturated CdTeZnTe solid solutions in the temperature range 743-848 K was measured by an electrochemical technique using LiCl KCl + 5 wt% ZnCl2 as the molten salt electrolyte. The activity of cadmium was estimated from hypothetical e.m.f. values and also by Gibbs-Duhem integration. The activity values of Zn and Cd calculated at different temperatures were used to obtain various partial and excess molar thermodynamic quantities, namely ΔGMZn, ΔGXSZn, ΔHMZn, ΔSMZn, ΔSXSZn, ΔGMCd, ΔGXSCd, ΔHMCd, ΔSMCd and ΔSXSCd. The thermodynamic data obtained in the present investigation are consistent with the view that the CdTeZnTe system consists of a single phase throughout the entire range of composition. © 1994.